SHAPING HIGH-PERFORMANCE WORK SYSTEMS THROUGH HRM PRACTICES - Gojny-Zbierowska, Milena (Journal of Positive Management, 2016)
Purpose: The analysis of the meaning of HPWS practices for employee and the identification of the positive human resource management practices essential for high performance work systems. Methodology: Literature review. Findings: Many research show that the HPWP implementation yields results in the form of increased productivity, increased in efficiency and benefits. There are many examples of the relationship between HPWS and various aspects of the functioning of the organization. In the debate on HPWS meaning for employee well-being there has been a polarization of opinions, some researchers have an enthusiastic attitude to the model, some are highly critical. Some aspects related to the system transformation decrease employee’s well-being and job satisfaction, some conversely, have a good effect on both dimensions. The effect is additionally conditioned by the status of the employee. Implications for practice: In order to boost the efficiency of the organization through HPWS, the system and the practice of HRM should be individually designed relevant to the company conditions in acceptable to the organization and feasible way, and then it should be implemented in accordance with the adopted assumptions.